Catalpol ameliorates psoriasis-like phenotypes via SIRT1 mediated suppression of NF-κB and MAPKs signaling pathways - Aimin Liu; Buxin Zhang; Wei Zhao; Yuanhui Tu; Qingxing Wang; Jing Li (Taylor & Francis, 2020)
Psoriasis is a chronic inflammatory skin disease that affects approximately 2% of worldwide population, and causing long-term troubles to the patients. Therefore, it is urgent to develop safe and effective therapeutic drugs. Catalpol is a natural iridoid glucoside, that has several remarkable pharmacological effects, however, whether catalpol can alleviated psoriasis has not been explored. The goal of the present work is to study the role of catalpol in psoriasis in vivo and in vitro. Imiquimod-induced psoriasis-like mice were applied with different concentrations of catalpol for 8 consecutive days. The severity degree of psoriasis was estimated and the skin pathological changes were detected by H&E staining. Also, TNF-α-stimulated keratinocytes were treated with different concentrations of catalpol, then the oxidative stress and inflammation factors, as well as the expression of SIRT1 and activation of NF-kB and MAPK pathways were measured. The results showed that catalpol reduced the erythema, scaling, ear thickness, and changed pathological phenotypes in the lesioned skin region in mice. Treatment with catalpol significantly suppressed the oxidative stress and inflammatory reactions in vivo and in vitro, as reflected by the decreased secretion or expression of oxidative stress indicators and proinflammatory factors. Furthermore, the SIRT1 was up-regulated and the NF-κB and MAPKs signaling pathways were suppressed by the treatment of catalpol in vivo and in vitro. In summary, our data suggested that catalpol may have a therapeutic property of psoriasis by ameliorating oxidative stress and inflammation partly through SIRT1 mediated suppression of NF-κB and MAPKs pathways.
Abbreviation: CAT: catalase; ELISA: enzyme-linked immunosorbent assay; GSH: glutathione; HRP: horseradish peroxidase; IMQ: imiquimod; JNK: c-Jun NH 2-terminal kinases; MAPKs: mitogen-activated protein kinases; MDA: malondialdehyde; NC: negative control group; NF-kB: nuclear factor kappa B; PASI: psoriasis area and severity index; PVDF: polyvinylidene difluoride membranes; qRT-PCR: quantitative real time polymerase chain reaction; ROS: reactive oxygen species; SDS-PAGE: sodium dodecyl sulfate-polyacrylamide gel; SIRT1: silent information regulator 1; SOD: Cu/Zn superoxide dismutase
Keywords: Biochemistry; Space Science; Medicine; Microbiology; Genetics; Molecular Biology; Immunology; Developmental Biology; Mental Health; Infectious Diseases